Motivational Strategies and Teachers’ job Performance in Post-Basic Education and Career Development (PBECD), Nigeria - Josiah, Hayab Fortune; Audu, Bandekaji Chris; Ogunode, Niyi Jacob (International Journal on Integrated Education, 2023)
This paper discussed motivational strategies and teachers’ job performance in Post-Basic Education and Career Development (PBECD) in Nigeria. Secondary data was adopted for the paper and the secondary data were sourced from print and online publications. The paper identified decision making, payment of salaries and allowance, provision of conducive environment, provision of instructional resources, promotion and award, appreciation, praise, commendations as motivational strategies for improving the job performance of teachers in Post-Basic Education and Career Development (PBECD). Based on this findings, the suggested the following: that government should organize training for school administrators of Post-Basic Education and Career Development (PBECD) on monetary and non-monetary motivational strategies and on how they can use them effectively to motivate teachers working on them. School administrators of Post-Basic Education and Career Development (PBECD) should ensure they use more of non-monetary motivational strategies in the schools because studies showed that teachers love when their boss appreciate their efforts by thanking them praising them, giving them awards, commendation letters and promotions. School administrator should ensure staff are promoted as of when due.